2015
DOI: 10.1007/s00018-015-1964-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional roles of connexins and pannexins in the kidney

Abstract: Kidneys are highly complex organs, playing a crucial role in human physiopathology, as they are implicated in vital processes, such as fluid filtration and vasomotor tone regulation. There is growing evidence that gap junctions are major determinants of renal physiopathology. It has been demonstrated that their expression or channel activity may vary depending on physiological and pathological situations within distinct renal compartments. While some studies have focused on the role of connexins in renal physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 76 publications
(124 reference statements)
0
19
0
Order By: Relevance
“…Previous studies showed that perfusion of tubules expressing Cx30, causes ATP release into the tubular lumen . Renal Cx30 expression is restricted to the connecting tubule and CD . In contrast, pannexin‐1 and Cx37 are expressed ubiquitously along the nephron, whereas Cx30.3 is confined to CD .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that perfusion of tubules expressing Cx30, causes ATP release into the tubular lumen . Renal Cx30 expression is restricted to the connecting tubule and CD . In contrast, pannexin‐1 and Cx37 are expressed ubiquitously along the nephron, whereas Cx30.3 is confined to CD .…”
Section: Discussionmentioning
confidence: 99%
“…120 Pannexin-1, recently identified as a target of caspase-11-mediated pyroptosis, 58 has an extensive distribution at the apical side of tubular epithelial cells throughout the nephron but also on peritubular capillaries. 127 In Panx1 -/-mice, 30% more ATP was found in the urine as compared with wild-type mice, 127 which underscores their role as membrane channels under physiological circumstances, 128 but a possible role as pores during pyroptosis in various renal pathologies has not been elucidated yet. We were unable to find studies that investigated the role for gasdermin D in renal diseases.…”
Section: Pyroptosis and Putative Implications For Renal Diseasesmentioning
confidence: 96%
“…This cell-based therapy, especially using the mononuclear cell fraction, has shown to improve regeneration of multiple tissues under pathological conditions [44]. A recent study provided evidence that both Cx40 and Cx37 participate in endothelial nitric oxide synthase (eNOS) regulation in vivo, where in mice subjected to the 2K1C procedure, the interaction of Cx40 and Cx37 with eNOS was enhanced, resulting in increased nitric oxide (NO) release [45]. Mice lacking Cx40 featured decreased levels of eNOS [45], and in different models of hypertension, Cx37 selectively participates from an altered expression of AT2R [46].…”
Section: Connexins In Hypertensive Nephropathymentioning
confidence: 99%
“…A recent study provided evidence that both Cx40 and Cx37 participate in endothelial nitric oxide synthase (eNOS) regulation in vivo, where in mice subjected to the 2K1C procedure, the interaction of Cx40 and Cx37 with eNOS was enhanced, resulting in increased nitric oxide (NO) release [45]. Mice lacking Cx40 featured decreased levels of eNOS [45], and in different models of hypertension, Cx37 selectively participates from an altered expression of AT2R [46]. In addition, the amount of Cx43 is increased in inflammatory processes in damaged renal tubules and in interstitial cells in human kidneys [47].…”
Section: Connexins In Hypertensive Nephropathymentioning
confidence: 99%